Die Hüter des Hades. Zur Bedeutung und Interpretation der homerischen Kimmerier - Michaela Rücker (Digital Classics Online)
This paper deals with the Homeric Cimmerians, who were located at the end of the world, on the doorsteps to Hades. At the beginning of the work, it was necessary to build up a concept of research 1st to find the relevant sources and 2nd to distinguish the mythical Cimmerians from the historical. Tools from the project eAQUA and eXChange illustrate the selection of sources.